Quantifying sustainability metrics for trunkline bridges in the Mountain Plains region - Gopi, Vaishak, author; Van de Lindt, John W., advisor; Senior, Bolivar, advisor; Strong, Kelly, committee member (Colorado State University. Libraries, 2016)
The use of millions of cubic yards of concrete and steel to support the U.S infrastructure may result in a significant negative impact on the environment. CO2 released by the construction processes as well as the material production, is taking a toll on the environment. This study is aimed at developing a ranking system to determine the emission of CO2 for bridges and rank them based on their CO2 emission. Firstly, in order to accomplish this objective, rating systems for buildings from around the world were analyzed for common attributes applicable to bridges. Secondly, a sample of bridges from the state of Colorado was selected and analyzed for their sustainability by only considering their main materials and a ranking system based on the emission of CO2 was developed. This served as the first step in developing a rating system for bridges in Colorado where only the CO2 emission from the production and transport of concrete and steel were considered. This rating system can be further developed to include CO2 emissions from construction processes, demolition and disposal and other factors that contribute to sustainability, but its current version is intended only to provide an example of an approach for development of a ranking system.
Keywords: Colorado; prestressed bridges; sustainability metrics; environmental analysis tool; bridge sustainability; steel bridges